Non-invasive Spatial Mapping of Frequencies in Atrial Fibrillation: Correlation With Contact Mapping - Rodrigo, Miguel; Waddell, Kian; Magee, Sarah; Rogers, Albert J.; Alhusseini, Mahmood; Hernandez-Romero, Ismael; Costoya-Sánchez, Alejandro; Liberos, Alejandro; Narayan, Sanjiv M. (Frontiers in Physiology, 2021)
Introduction: Regional differences in activation rates may contribute to the electrical substrates that maintain atrial fibrillation (AF), and estimating them non-invasively may help guide ablation or select anti-arrhythmic medications. We tested whether non-invasive assessment of regional AF rate accurately represents intracardiac recordings. Methods: In 47 patients with AF (27 persistent, age 63±13 years) we performed 57-lead non-invasive electrocardiographic Imaging (ECGI) in AF, simultaneously with 64-pole intracardiac signals of both atria. ECGI was reconstructed by Tikhonov regularization. We constructed personalized 3D AF rate distribution maps by Dominant Frequency (DF) analysis from intracardiac and non-invasive recordings. Results: Raw intracardiac and non-invasive DF differed substantially, by 0.54 Hz [0.13 – 1.37] across bi-atrial regions (R2=0.11). Filtering by high spectral organization reduced this difference to 0.10 Hz (cycle length difference of 1 - 11 ms) [0.03 – 0.42] for patient-level comparisons (R2=0.62), and 0.19 Hz [0.03 – 0.59] and 0.20 Hz [0.04 – 0.61] for median and highest DF respectively. Non-invasive and highest DF predicted acute ablation success (p=0.04). Conclusions: Non-invasive estimation of atrial activation rates is feasible and, when filtered by high spectral organization, provide a moderate estimate of intracardiac recording rates in AF. Non-invasive technology could be an effective tool to identify patients who may respond to AF ablation for personalized therapy